Evaluation of an acrylic acid hydrogel dosimeter for 3-D dose verification in radiotherapy using MRI - Ihssan S. Masad; Khalid A. Rabaeh; Samer I. Awad; Akram A. Almousa; Ahmed M. Masawi; M. Abdullah Al Kafi; Samer M. Alheet; Abdallah J. Nofal; Belal Moftah (PLoS ONE, 2026)
Gel dosimeters are commonly used to verify the dose distribution and consequently, ensure the accurate delivery of the dose as planned, which is very critical for the success of the radiotherapy. The current study aims to investigate the feasibility of using the magnetic resonance imaging (MRI)-based relaxation rate maps (R2 maps) of the novel acrylic acid with organic glucose polyvinyl alcohol (ACAGLPVA) hydrogel dosimeter for 3-D dose verification. The (ACAGLPVA) hydrogel was prepared and scanned with a 3-T MRI, prior to irradiation, using a spin-echo (SE) sequence. A series of 30 images with different echo times (TE) were acquired in order to generate R2 maps. The hydrogel was then irradiated with a maximum dose of 8 Gy using a CyberKnife system and the same MRI scans were acquired again for the irradiated gel phantom. The measured dose distributions obtained from R2-MRI maps were compared, using 2-D and 3-D Gamma analyses with 3% dose difference and 3-mm distance-to-agreement criteria, to those calculated from the treatment planning system (TPS). Results have shown high spatial agreement between the dose distributions calculated from TPS and the dose distributions derived from R2 maps, particularly in high-dose regions. The 3-D Gamma analysis achieved pass rates exceeding 90% across all planes for all evaluated dose levels—namely 90%, 70%, 50% and 20% of the maximum dose in the axial plane, as well as 90%, 70% and 50% of the maximum dose in the coronal and sagittal planes. In conclusion, based on the analysis of R2-MRI maps, this study has demonstrated the reliability of using the novel (ACAGLPVA) hydrogel dosimeter as an accurate tool for 3-D verification of radiotherapy treatment plans.